PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN GUGUS II KECAMATAN MADAPANGGA TAHUN PELAJARAN 2020/2021 - Novi Nurhandayani; Arjudin Arjudin; Heri Hadi Saputra (Renjana Pendidikan Dasar, 2021)
In a learning process, students are still able to understand a concept through what is seen in real or concrete terms. Therefore, an elementary school teacher must be creative and innovative in teaching mathematics to students. Mathematics learning designed and implemented monotone and without the application of innovative learning approaches can result in students being less motivated in understanding the material provided by the teacher. So it requires an approach that can foster motivation and student learning outcomes of mathematics as a whole, namely the realistic mathematical approach. The purpose of this study was to determine the effect of the realistic mathematics approach on the motivation and mathematics learning outcomes of fourth grade students of SDN Cluster II Madapangga Sub-district 2020/2021 school year. The results of this study are expected to be useful theoretically and practically. This type of research is an experimental study with a quasi-experimental design type nonequivalent control group design. The population of this study was all fourth grade students of SDN cluster II Madapangga Sub-district 2020/2021 school year consisting of SDN Rade, SDN Inpres Rade and SDN Inpres Sambitangga. The sampling technique of this research is probability sampling type cluster random sampling. The data collection methods are observation, questionnaire and test. Data analysis was performed by normality test, homogeneity test and hypothesis testing using the polled variance t-test formula. Based on the posttest results, the average value of learning motivation in the experimental class was 122, while the control class average was 117. For the average value of mathematics learning outcomes in the experimental class was 82,7, while the control class average was 73,5. So the experimental class had a higher average value than the control class. Hypothesis testing at a significant level of 5% produces t_count = while t_ (table) = , in other words, t_count> t_tabel. Based on the testing criteria namely if t_count> t_table then HO is rejected and Ha is accepted. Therefore, it can be concluded that there is a positive and significant effect of the use of the realistic mathematics approach on the motivation and mathematics learning outcomes of fourth-grade students of SDN Cluster II Madapangga Sub-district academic year2020/2021.